Get The Teachers Prepared First - New Straits Times, Malachi Edwin Vethamani (2008)
ENGLISH LANGUAGE education in Malaysia is again the focus of attention Even as the government is considering whether Mathematics and Science should continue to be taught in English the Education Minister was reported to be considering making English Literature a subject at the primary school level.